Substâncias encontradas em algas rodofíceas do litoral paraibano e do Mar Jônico - Grécia - Tomaz, Anna Cláudia de Andrade (2012)
Marine organisms are potentially prolific sources of bioactive secondary metabolites that might represent useful leads in the development of new pharmaceutical agents. Red algae are considered the main source of many biologically active metabolites in comparison to other algal classes and they comprise about 8,000 species. In northeastern Brazil littoral areas, red seaweeds like Gracilaria are abundant species. The red algae Gracilaria birdiae, Gracilaria caudata, Gracilaria cervicornis and Gracilaria domingensis (family Gracilariaceae) collected on the coast of Paraíba were targets of our scientific interest in order to know their active constituents due to the lack of chemical and pharmacological data in scientific literature. A collaboration with Professor Vassilios Roussis, University of Athens (Greece), through financial support of the Programa de Doutorado no País com Estágio no Exterior (PDEE/CAPES) was added to this research. Through this partnership, the phytochemical study of the red alga Sphaerococcus coronopifolius (family Sphaerococcaceae) collected in the Ionian Sea (Greece) was also performed since this species has been subject of previous chemical investigations and has an acknowledged excellent phytochemical profile. Suitable chromatographic and spectroscopic methods were used to accomplish those objectives. The analysis of the algae from the genus Gracilaria allowed the identification of a fraction rich in hydrocarbons, and the isolation and identification of a sterol and a fatty acid from the alga G. caudata, as well as the analysis and characterization of methyl esters of fatty acids of the CH2Cl2/MeOH extracts of the four species under study. The study of the alga Sphaerococcus coronopifolius resulted in the isolation and purification of twenty terpenes, being three new ones, one first isolated in the species, one first isolated in the species when collected in the Ionian Sea (Greece) and other re-isolated in order to obtain material for biological tests.